pTARGEX vectors: a versatile toolbox for plant-based protein expression - Chartrand-Pleau, Camille; Gallipeau-Burns, Emily; Jain, Ananya; Boddy, Victor; Fakhouri, Patrick; Rehmani, Sarah; Thomas, Teagan; Drapeau, Michelle; VanderBurgt, Jordan T.; Boudigou, Arnaud; Damry, Adam M.; MacLean, Allyson M. (Frontiers in Synthetic Biology, 2025)
The ability to express heterologous proteins in specific plant tissues and subcellular compartments is critical for advancing plant-based biotechnologies and biopharming research. Here, we present the “pTARGEX” series, a versatile toolkit designed to enable targeted protein expression within the leaves and roots of plants. These vectors incorporate subcellular targeting sequences to direct proteins of interest to the apoplast (pTARGEX-APO), cytoplasm (pTARGEX-CYT), chloroplast (pTARGEX-CHL), endoplasmic reticulum (pTARGEX-ER), or vacuole (pTARGEX-VAC). Streamlining workflow, the pTARGEX vectors encode an mCherry dropout cassette with a SapI restriction enzyme site to enable red/white screening in Escherichia coli, and an eGFP reporter gene that is constitutively expressed in planta to serve as an inbuilt marker for monitoring of successful transformation. This innovative vector series offers users an accessible, versatile platform for plant-based heterologous protein production, facilitating research and applications in systems biology, synthetic biology, and plant biotechnology.